Pergulatan Mazhab Hukum dalam Pengadaan Tanah Milik Masyarakat Adat untuk Kepentingan Umum: The Struggle of Legal Schools in Procuring Land Owned by Indigenous Peoples for Public Interest - Kukuh Tejomurti; Denie Amiruddin; Andi Sasongko; Imam Sukadi (Warkat, 2022)
In the discourse on land acquisition for development in the public interest, problems often arise regarding the amount of compensation to land rights holders. The problem becomes even more widespread when the land acquired intersects with and originates from customary land. This article aims to provide an elaboration of thoughts from a philosophical perspective on law and justice, especially on positive legal formalism in the implementation of land acquisition belonging to customary law communities in Indonesia. The research used in this article is normative legal research using a legislative approach, a conceptual approach and a case approach. The legal materials used are primary legal materials and secondary materials which are connected with schools of legal philosophy, such as the Natural Law School, Legal Positivism, and the Historical School. The research results show that the sharp gap between the legal positivism school and the historical legal school lies in the sources and forms of law. If legal positivism prioritizes formal forms and the authoritative institutions that create them, then the historical legal school states that laws are not made but are found in society. Sociological Jurisprudence describes a "middle way" to bridge the flow of historical law in traditional law communities whose existence is respected in the formation of law to provide just legal certainty. In the context of Indonesia, which has a civil law tradition, we can consider the formation of legislation as an important component for the social engineering process. Therefore, laws and regulations related to land acquisition should involve indigenous communities in the formation process because most of Indonesia's territory is still customary territory/land in the form of fields, forests, and so on.